Diseño del sistema fijo contra incendios para el Edificio de Oficinas Centrales del Benemérito Cuerpo de Bomberos de Costa Rica - Vargas-Zúñiga, Fernando (Instituto Tecnológico de Costa Rica, 2018)
This specialty practice report is a step-by-step design and calculations for a complete fire protection system based on automatic sprinklers. The design was made for the Building of Central Offices of the Fire Department of Costa Rica, a building that could be called the "headquarters" of the authority having jurisdiction (AHJ) precisely in the subject that talks about this text, the fire prevention. It is not only a design of a fire sprinkler system, it is a complete design of a fire protection system, from the positioning and location of the sprinklers in order to deal with the obstructions to the discharge pattern, the sprinkler piping system, the design of the cabinets system, hoses and standpipe, the hanging, bracing, and restraint of system piping, the pumps room and the selection of a specific listed fire pump and its accessories, the water tank, the underground fire service mains, the fire extinguishers locations that the regulations dictates and to finally all the hydraulic calculations that this entails, as done by hand with the detailed worksheets of the NFPA as also using AutoSPRINK, the best the simulation software for fire protection systems.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Sistemas; Incendios; Gabinetes; Research Subject Categories::TECHNOLOGY::Engineering mechanics